Tipologi Konflik Berbasis Sumber Daya Pangan di Wilayah Perkebunan Sawit - . Sumardjo; Sutisna Riyanto; Amiruddin Saleh; . Dahri; Adi Firmansyah (Institut Pertanian Bogor, 2014)
This research aims: 1) to analyze typology characteristic and conflict mapping in oil palm plantations; 2) to analyze the effectiveness of conflict resolution processes that have taken; 3) to formulate a conflict resolution strategy that is appropriate to the conflict type through collaborative approach base on potential resource and local knowledge. Primary data collected by interviews with local government officials, key figures, and village leaders. Secondary data obtained from village offices, BPS, texbooks, journals, or data from the internet that contains research results related. Data collection techniques used are a combination of the method of triangulation to obtain accurate data. The data collected and processed in a descriptive analysis of quantitative data supporting. Conflict analysis method used in this study is an analysis of the mission and vision conflict phenomena, analyzes aspects of change, stakeholders analysis, perception analysis, analysis of issues, interests analysis, strategy analysis, analysis of engagement, analysis of potential allies, risk analysis, action analysis, and valuation analysis. The results of this study indicate that the conflict in the Sosa, North Sumatera, has come to the level of